GATA transcription factors in the developing and adult heart - Pikkarainen, Sampsa; Tokola, Heikki; Kerkelä, Risto; Ruskoaho, Heikki (Cardiovascular research, 2004)
During the past decade, emerging evidence has accumulated of different nuclear transcription factors in regulation of cardiac development and growth as well as in cardiac hypertrophy and heart failure. GATA-4, -5 and -6 are zinc finger transcription factors that are expressed in the developing heart and GATA-4 and -6 continue expression in the adult cardiac myocytes. GATA-4 and -6 regulate expression of several cardiac-specific genes, and during murine embryonic development, GATA-4 is essential for proper cardiac morphogenesis. In support of this, mutations of gene for GATA-4 or for its cofactors have been associated with human congenital heart disease. Pressure overload of the heart in vivo as well as hypertrophic stimulation of cardiac myocytes in vitro provide adequate stimulus for activation of GATA-4. Activity of GATA-4 transcription factor is subject to regulation at the level of gene expression and through post-translational modifications of GATA-4 protein. A number of genes induced during cardiac hypertrophy possess functional GATA sites in their promoter region and cardiac-specific overexpression of GATA-4 or -6 leads to cardiac hypertrophy. In addition, a pattern of interactions between GATA-4 and its numerous cofactors have been identified, showing an increasing complexity in regulatory mechanisms. The present review discusses current evidence of the role and regulation of GATA transcription factors in the heart, with an emphasis in the GATA-4 and development of cardiac hypertrophy.